Effect of opioid-free anesthesia on postoperative nausea and vomiting after gynecological surgery: a systematic review and meta-analysis - Zhang, Zheng; Li, Chengwei; Xu, Lin; Sun, Xinyi; Lin, Xiaojie; Wei, Penghui; Li, Jianjun (Frontiers in Pharmacology, 2024)
Background: Postoperative nausea and vomiting (PONV) is a common complication, that can reduce patient satisfaction and may lead to serious consequences, such as wound dehiscence. Many strategies have been proposed to prevent PONV; however, it remains common, especially in high-risk surgeries such as gynecological surgery. In recent years, opioid-free anesthesia has been widely studied because it minimizes adverse reactions of opioids, such as nausea, vomiting, and itching; however, conclusions have been inconsistent. Therefore, we conducted this meta-analysis to investigate the effects of opioid-free anesthesia on PONV in patients undergoing gynecological surgery. Methods: A systematic search of the PubMed, Web of Science, Cochrane Library, and Embase databases, from inception to 28 August 2023, was performed. Keywords and other free terms were used with Boolean operators (OR and, AND) to combine searches. This review was performed in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results: Six studies involving 514 patients who underwent gynecological surgery were included. The forest plot revealed that the incidence of PONV (risk ratio = 0.52; p < 0.00001) and consumption of postoperative antiemetics use (risk ratio = 0.64; p = 0.03) were significantly lower in the opioid-free anesthesia group. In addition, opioid-free anesthesia improved the quality of recovery (mean difference = 4.69; p < 0.0001). However, there were no significant differences in postoperative pain scores (mean difference = 0.05; p = 0.85), analgesic use (risk ratio = 1.09; p = 0.65), and the time of extubation (mean difference = −0.89; p = 0.09) between the opioid-free anesthesia and control groups. Conclusion: OFA reduces PONV and the use of antiemetic drugs. In addition, it improves the quality of postoperative recovery. However, OFA can not reduce the postoperative pain scores, analgesic use and the time of extubation. Due to the strength of the evidence, we cannot support OFA as an ideal anesthesia method in gynecological surgery, and the implementation of anesthesia strategies should be case-by-case. Systematic Review Registration: [https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=462044], identifier [CRD42023462044]